Adherence to HIV post-exposure prophylaxis in a specialized service in São Paulo, Brazil - Marcos Morais Santos Silva; Luciane Simões Duarte; Lucia Yasuko Izumi Nichiata (Journal of Infection in Developing Countries)
Introduction: The effectiveness of human immunodeficiency virus (HIV) post-exposure prophylaxis (PEP) depends on adherence to the protocol, which includes taking antiretrovirals (ARVs) and attending visits. We examined the adherence rate to antiretroviral agents and follow-up visits identifying the associated characteristics of adherence and the reasons for not attending HIV PEP consultations in a specialized service in São Paulo, Brazil.